1993
DOI: 10.1002/acp.2350070203
|View full text |Cite
|
Sign up to set email alerts
|

Mental reinstatement of context: A technique for interviewing child witnesses

Abstract: The effectiveness of mental reinstatement of context as a technique for interviewing child witnesses was examined. Adult, 6-year-olds and 1 I-year-olds viewed a film and were interviewed in one of three conditions; (1) free recall, (2) mental reinstatement of the context in which the film was viewed or (3) a series of specific questions about the film. In terms of correct information recalled, mental reinstatement of context and specific questions produced more correct responses than did free recall. In terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 10 publications
(21 reference statements)
4
42
4
Order By: Relevance
“…Moreover, our results do not conflict with research in which young children were found to use and profit from contextual information (e.g., Dietze & Thomson, 1993;Wilkinson, 1988). In these previous studies, either the contextual information was present throughout the recall phase (as in the case of physical context reinstatement), or specific mental-reinstatement instructions or questions were introduced before the recall phase to reactivate the contextual information.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Moreover, our results do not conflict with research in which young children were found to use and profit from contextual information (e.g., Dietze & Thomson, 1993;Wilkinson, 1988). In these previous studies, either the contextual information was present throughout the recall phase (as in the case of physical context reinstatement), or specific mental-reinstatement instructions or questions were introduced before the recall phase to reactivate the contextual information.…”
Section: Discussioncontrasting
confidence: 53%
“…From a more applied perspective, the results suggest that in eyewitness situations, in which access to the original encoding context is often impaired, interrogators may indeed trigger children's memory for critical information through guided retrieval of related information. Yet our results also suggest that mainly older children would benefit from such guided retrieval, and that other techniques, such as mental-reinstatement techniques (Dietze & Thomson, 1993), might be necessary to improve eyewitness testimony in younger children. The present findings thus provide important clues and restrictions for the further development and…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, the effects of the MRC when used with typically developing children are somewhat mixed. Some studies have found the procedure beneficial when compared to standard interview conditions that do not include context reinstatement (Dietze & Thomson, 1993;Dietze et al, 2008;Dietze et al, 2010;Hayes & Delamothe, 1997;Hershkowitz, Orbach, Lamb, Sternberg, & Horowitz, 2001;Milne & Bull, 2002), while others have failed to find a positive effect (e.g., Darwinkel, Powell & Sharman, 2014;Dietze, Powell & Thomson, 2010;Milne & Bull, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Child witnesses have to receive (understand), and then implement (apply) a series of subjective instructions, which require significant language processing capacity and unimpaired attention and concentration abilities (see Dando, 2013;Dietze, & Thomson, 1993). MRC typically takes in excess of 10 minutes to implement, and so for both typically developing children and children with ASD is at best cognitively demanding, although some researchers have reported that it can improve remembering (see Dietze, & Thomson, 1993, although also see Hershkowitz et al, 2001 Dando, 2013;Dando, Wilcock & Milne 2009;Dando, Wilcock, Milne, & Henry, 2009;Dando, Wilcock, Behnkle, & Milne, 2011). Participants interviewed using the Sketch-RC typically performed equal to, or better than, those interviewed using MRC for the amount of correct information elicited, with no increase in the reporting of erroneous items (erroneous information is discrepant from that which occurred in the stimulus).…”
Section: Introductionmentioning
confidence: 99%